Pengaruh Profitabilitas, Leverage, Dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Perusahan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2022 - Elex Sarmigi; Endah Sri Wahyuni; Maryanto Maryanto; Alek Wissalam Bustami (Program Studi Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
This study examines the effect of profitability ratios, namely return on assets (ROA), leverage ratios, debt to equity ratios (DER), firm size, and total assets, on earnings management in banking companies listed on the Indonesian stock exchange. The population in this study are all banks listed on the Indonesian stock exchange. In contrast, the sample of this study is banks that consistently published their financial statements on the Indonesian stock exchange in 2015-2022. Therefore, 10 banks were obtained to be used as samples, each for 8 years. The data analysis tools used are multiple linear regression, t, and F tests. This study found that partial profitability has a positive but insignificant effect on earnings management, while leverage and firm size have a negative and significant effect. Simultaneously, profitability, leverage, and company size affected earnings management in banking companies listed on the Indonesian stock exchange in 2015-2022, with a magnitude of effect of 87,8%.